(untitled) (Global Journal of Science Frontier Research, 2018)
The conclusion about the absence in them of the mathematical means of the adequate description of passage from one inertial reference system to another because of the use by them of particular derived field functions on the time, which completely tie electrodynamic process to one concrete frame of reference, is made on the basis of the critical analysis of extraction from the equations of the electrodynamics of ideas about the space and period. Is proposed new approach to the development of the mathematical apparatus for electrodynamics in the direction of the more adequate description of passage from one inertial reference system to another due to the introduction into the examination of the trans-coordinate equations, which use new Galilean and trans-coordinate derivatives of field functions.